DETERMINANTS OF AUDITOR EXPERTISE - Bonner, Se; Lewis, Bl (Journal of Accounting Research, 1990)
In this study, we explore a view of expertise in which specific experiences and training create knowledge, and knowledge is combined with innate ability to perform specific audit tasks. Specifically, we test the extent to which we can explain cross-sectional variation in auditors' performance in several audit tasks using various types of knowledge and ability measures that have been identified in the psychology literature as important determinants of auditor expertise. We compare these results to the explanatory power of a simple measure of general audit experience. Our results indicate that, although more experienced auditors outperform less experienced auditors on average (and given our performance criteria), knowledge and innate ability provide a better explanation of variation in performance. Part of the motivation for this paper is to distinguish between general and expertise in the performance of information-processing tasks. Early studies of human information processing in accounting examined the effect of on performance in audit tasks (see, for example, Ashton and Brown [1980], Hamilton and Wright [1982], and Messier [1983]). Implicit in this research is the notion that . . a primary determinant of improved expertise ... is experience (Hamilton and Wright [1982, p. 757]). The reasoning behind this notion is that knowledge can be gained through and many audit tasks are knowl-